Factors related to the nutritional status of children under five in the HDSS Sleman working area - Rania Aisyah Herima; Hartriyanti, Yayuk; Ermamilia, Aviria (BKM Public Health and Community Medicine, 2021)
Background: The nutritional status factors of children under five are divided into two categories: direct factors (history of infectious diseases, history of birth weight, and food intake) and indirect factors (household income, mother's occupation, mother's education, father's occupation, family members number, and history of exclusive breastfeeding and complementary feeding). The achievement of good nutritional status in children under five in Sleman Regency is not optimal. Meanwhile, the nearest academic institution is expected to be able to contribute to solving this problem through a science-based approach. Objectives: To determine the prevalence of nutritional status and factors related to the nutritional status of children under five in the HDSS Sleman working area. Methods: The sample of this study was 103 toddlers aged 12-59 months who lived in Sleman Regency with a purposive sampling technique. The design of this study is cross-sectional, with the bivariate test used is the Fisher's Exact test. Results: The prevalence of overweight and obesity, which includes overweight and obesity, is four people (3.88%), and good nutrition is 95 people (92.23%). Four people (3.88%) were malnourished. Factors related to the nutritional status of children under five were a history of breastfeeding and complementary feeding (p=0.008). In addition, from other direct and indirect factors, no significant relationship was found with the nutritional status of children under five in the HDSS Sleman working area. Conclusion: Most toddlers in the Sleman HDSS work area have good nutritional status (92.23%). Factors related to the nutritional status of children under five are the history of breastfeeding and complementary feeding, which are indirect factors.